Pengaruh Model Pembelajaran Project Based Learning dalam Pembelajaran IPA terhadap Kemampuan Berpikir Siswa - Putri Qalbina; Defrian Melta; Rahmi Kurniati; Nosi Qadariah (Journal on Education, 2024)
In science learning, it is necessary to emphasize learning that refers to direct experience so that it can provide space for students to develop the ability to think, work and act scientifically in an integrated manner. To cultivate these thinking skills, a learning model is needed. One learning model that can improve students' thinking skills is Project Based Learning. The purpose of this study was to analyze the effect of Project Based Learning on students' thinking skills in science learning. The research method used is systematic literature review. The data used in this study were obtained from previous research, in the form of articles related to the Project Based Learning learning model and students' thinking skills. The results of the study show that some previous research literature has proven that project based learning can be applied to science learning and plays a role in improving students' thinking skills, both higher order, critical, and creative thinking skills.